IS, a global caliphate, and exceptionalism: an ideological criticism of the Islamic State’s rhetoric in Dabiq - Cutter, Dan (Kansas State University, 2017)
In July of 2014, a spokesperson for the Islamic State in Iraq and the Levant (ISIL) made a televised announcement that captured the attention of the world – the terrorist organization decided to tweak its name to simply the Islamic State (IS), to indicate its intention of moving beyond Iraq and the Levant and conquering the world. This shift in rhetoric, along with the phenomenon of Muslims and non-Muslims from Western nations leaving their homes, friends, and families behind to join IS, have prompted discussions and debates on what makes this terror group’s message so effective. In the days following IS’s name change, the first issue of its magazine Dabiq was published online through its Al-Hayat Media Center. With versions in English, Arabic, German, French, and more, the magazine gained notoriety for its high-production value. This study seeks to understand the ideology manifest in IS rhetoric in Dabiq, which makes it so captivating to both sympathizers and agitators alike. This study is an ideological criticism of six of the fifteen issues of Dabiq published; the six issues chosen were all released in relation to catalytic events perpetrated or claimed by the terror group. For instance, the November 2015 Paris attacks or the shooting in San Bernardino, CA, by a ‘radicalized’ couple who pledged allegiance to IS. This study unearthed major themes of political claims, religious appeals, and terrorist actions which IS uses to incite recruitment. This analysis identifies IS’s ideology as one of Political Islamist Terrorism, and concludes with implications concerning exceptionalism and the persuasive appeal of Dabiq.
Keywords: ISIS/ISIL/IS; Rhetoric; Terrorism; Magazine; Propaganda; ExceptionalismIdeology